Using Visualization as an Easy Way to Learn Programming Logic - Loo, Sze Phei (2009)
In the Information Technology (IT) education, from certificate level in colleges or educational institutions until degree level in universities, programming courses are essential to build students‘ logical thinking and to train their programming skills in creating different types of software. Unfortunately,programming courses often consist of higher failure rates than other computer science courses. In this research, problem in studying programming courses will be analysed through literature review. To improve and to aid the understanding of the essence of computer programming, an easy way to learn programming logic will be formulated focusing on providing visualization to aid the learning. This approach will be applied on a courseware prototype, presented and later evaluated by first year diploma computer science students. Brief on the results obtained.